Keunggulan L-PRF Dibandingkan P-PRF, PRFM, A-PRF, & I-PRF sebagai Cangkok pada Operasi Miringoplasti: Studi Penyembuhan Luka pada Perforasi Membran Timpani - Antonius Christanto; Risya Cilmiaty; Made Setiamika; Ratih Dewi Yudhani; Paramasari Dirgahayu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the advantages of Leukocyte-Platelet Rich Fibrin (L-PRF) application in myringoplasty surgery compared to other platelet concentrates such as Platelet-Rich Fibrin Membrane (PFRM), Advanced Platelet-Rich Fibrin (A-PRF), and Injectable Platelet-Rich Fibrin (I-PRF). The research method used is a qualitative literature review, collecting and analyzing data from recent scientific journals and clinical studies related to the use of L-PRF in tympanic membrane repair. The study finds that L-PRF, with its dense fibrin network and high content of leukocytes and growth factors, enhances tissue regeneration, angiogenesis, and epithelialization, which are critical for successful graft integration and faster healing after myringoplasty. Compared to other platelet concentrates, L-PRF offers better mechanical strength and a more sustained release of growth factors. Additionally, L-PRF reduces postoperative complications and improves hearing outcomes. Being an autologous biomaterial, it also reduces the risk of immune rejection. The findings suggest that L-PRF is a promising graft material in otologic surgery, though further clinical trials are needed to optimize its application protocols.